A review of the millipede fauna of Ethiopia, with the description of a new genus and species of the family Spirostreptidae (Diplopoda, Spirostreptida) - Golovatch, Sergei I.; Enghoff, Henrik; Korotayeva, Alyona M. (Zootaxa, 2026)
The known millipede fauna of Ethiopia is reviewed, and its provisional checklist currently contains fewer than 40 species. A new monotypic genus of Spirostreptidae is described from an evergreen tropical forest in Oromiya State, Ethiopia: Altisternostreptus gen. nov., with A. harenna sp. nov. as the type species. The new genus differs from other genera of Spirostreptidae/Perustreptinae/Perustreptini primarily by: (1) the remarkably high and narrow gonopod sternum, coupled with the combination of the body ring pleura meeting and fusing in the midline behind the second pair of legs of each ring; (2) the gonopod coxal metaplica showing both a prominent mesal (map) and a smaller lateral (lap) process apically, lap being remarkably unciform and directed apicad; (3) the gonopod telopodite very long and slender, devoid of an antetorsal process or spine, but at about 1/3 of its exposed part markedly torsate through 360° and then coiled into a complete and tight circle; (4) the post-torsal part of the telopodite very simple, subflagelliform, with no side branches apart from a small post-torsal fold (ptf) that tightly envelopes the telopodite at about its midway and distal to the twist on the caudal face; and (5) the efferent canal (= seminal groove) in the gonopod telopodite unbranched, terminating on a simple, barely bifid and only slightly sigmoid tip.